The handbook of art and design librarianship - Glassman, Paul; Dyki, Judy (Chicago Neal-Schuman, an imprint of the American Library Association, 2017)
The handbook examines methods of innovative librarianship in academic and art school libraries. Serving as a field guide to academic art libraries in the twenty-first century, it integrates theory and practice as demonstrated by creative professionals working in the field of art librarianship. While much attention has been paid to art librarianship as it exists in museum settings, the focus on academic art and design school information services has not been as intensive. This essential handbook addresses that gap in the professional literature and examines methods of innovative librarianship in academic and art school libraries. The book offers guidelines for information professionals working in art and design environments who support and anticipate the information needs of artists, designers, architects, and the historians who study those disciplines.
Part I: Roles and responsibilities. The governance and administration of the art and design library / Paul Glassman -- Evolution not revolution : evolving trends in art and design libraries / Barbara Opar -- Expanding roles for fine arts liaison librarians : re-visioning the liaison model / Stephanie Kays -- Accreditation and visual arts libraries / Judy Dyki -- Design thinking for design librarians : rethinking art and design librarianship / Rachel Ivy Clarke -- Part II: Materials and collection management. Visual resources : from analogue to digital and beyond / Molly Schoen -- Developing digital collections / Greta Bahnemann and Jeannine Keefer -- Inspirational encounters : the management and use of archives and special collections in the art and design library / Jess Crilly, Gustavo Grandal Montero and Sarah Mahurter -- What is special about special collections? / Lee Sorensen -- Artists' books in the art and design library / Tony White -- Art documentation : exhibition catalogues and beyond / Gustavo Grandal Montero -- Tactile libraries : material collections in art, architecture and design / Rebecca Coleman and Mark Pompelia -- Seeing the bigger picture : archival description of visual information / Alyssa Carver -- Part III: Teaching and learning. Embedded in their world : moving mentally into the studio environment / Michael A. Wirtz -- Teaching with threshold concepts and the ACRL Framework in the art and design context / Alexander Watkins -- Teaching by the book : art history pedagogy and special collections / Sandra Ludig Brooke -- Metaliteracy in art and design education : implications for library instruction / Leo Appleton -- The art of evidence : a method for instructing students in art history research / Catherine Haras -- 'I want students to research the idea of red' : using instructional design for teaching information literacy in the fine arts / Katie Greer and Amanda Nichols Hess -- Cultural differences and information literacy competencies / Nancy Fawley -- Part IV: Knowledge creation. The ever-shifting landscape : mapping the present and future of digital art histories / Colin Post -- Critical cARTography : mapping spaces for dialogue about identity and artistic practices / Andy Rutkowski and Stacy R. Williams -- More than just on the walls : enhancing fine arts pedagogy in the academic library space / Rachael Muszkiewicz, Jonathan Bull and Aimee Tomasek -- Beyond the monograph? Transformations in scholarly communication and their impact on art librarianship / Patrick Tomlin -- Part V: The physical environment. New, renovated and repurposed library spaces : responding to new demands / Leo Appleton, Karen Latimer and Pat Christie -- Why is that column in the middle of the room? Success in creating classrooms for library instruction / Paul Glassman -- Finding common ground : creating library spaces for collaboration / Beverly Mitchell -- Part VI: Promotion and sustainability. Marketing plans made simple / Paul Glassman -- Engaging with social media / Ken Laing and Hillary Webb -- Website strategies for art and design libraries / Judy Dyki -- Appendix: Library profiles / Beth Morris.
a"First published in the United Kingdom by Facet Publishing, 2017"--Title page verso.
Includes bibliographical references and index.
Keywords: Art libraries -- Handbooks, manuals, etc